Effect of Gap between Prefabricated Concrete Deck Elements on Stiffness of Composite Bridges - Abbas, A.; Ajwad, A.; Khan, M. A.; Aqdas, A.; Ilyas, U.; Rashid, M. U.; and, Abdullah; Adnan, M. A. (The Nucleus, 2019)
<span style="font-size: 10.0pt; font-family: 'Times New Roman',serif; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Composite bridges are a new dimension of today’s bridges, which involves two materials of different properties that are combined to give a unique property together. In this research, such a bridge made of Concrete and steel was chosen where the supporting medium was a steel beam with a concrete deck on top of it. One of the more advanced steps in this bridge was to prefabricate the concrete deck. The influence of the gap between the prefabricated concrete deck elements and its effect on the bridge stiffness was studied under serviceability loading. It was found out that increasing the gap did affect the stiffness of composite bridge. The deflection increased linearly with the increase in gap of concrete deck elements. Also when compared with the hand calculation, the results from ABAQUS showed presence of shear lag.